A horizontal mixer and a batch-to-horizontal mixer system increased the mix uniformity of free methionine in complete diets relative to a vertical mixer - L.E. Knarr; K.M. Bowen; E.B. Estanich; J.S. Moritz (Journal of Applied Poultry Research)
Summary: The coefficient of variation (CV) of a selected nutrient marker is commonly utilized to measure mix uniformity (MU) of a batch of feed, where a CV < 10 % is considered industry-acceptable. Mixer type and mix time (MTI) have been shown to affect mix uniformity (MU), however, data concerning mixing systems (MSY) are unavailable. Additionally, past research has shown that the selection of an appropriate CV marker is integral in properly evaluating MU. Two experiments were conducted to evaluate a vertical, horizontal, and transfer MSY on MU while utilizing inadequate or adequate MTIs for a corn-salt mixture (CSM) and complete diet (CD). Chloride ion (Cl−) was selected as the marker for the CSM, and crystalline DL-Methionine (Free Met) and crystalline l-Lysine-HCl (Free Lys) were selected as the markers for the CD. Increasing MTI decreased Cl− CV in the CSM (P = 0.020). An interaction between MSY and MTI affected Free Met CV in the CD (P = 0.007). The horizontal and transfer MSYs did not demonstrate changes in the Free Met CV when MTI was manipulated, whereas the vertical MSY provided decreased CV with increased MTI. The authors hypothesize that additional mixing during load-out and conveyance caused this interaction. However, no treatment provided a Free Lys CV < 10 %. These data suggest that Cl− and Free Met are appropriate markers for MU in CSMs and CDs respectively, transfer MSYs may improve the overall efficiency of feed manufacture, and evaluating MSYs as a whole may provide more representative evaluations of feed before animal consumption.